Last of her name - Khoury, Jessica, 1990- (Scholastic Press, an imprint of Scholastic Inc., 2019)
"Sixteen years ago, rebellion swept the galaxy known as the Belt of Jewels. Every member of the Leonov royal family was murdered--down to their youngest child, Princess Anya--making way for the Union government to seize power. But Stacia doesn't think much about politics. She spends her days half-wild, rambling her father's vineyard with her friends, Clio and Pol. That all changes when a Union ship appears burning through the sky, bearing the leader of the Union, the Direktor Eminent himself, who declares that Stacia's sleepy village is a den of empire loyalists. Even more shocking, the Direktor claims that Princess Anya Leonova is alive--and Stacia is the lost princess. As their home explodes into chaos, Pol smuggles Stacia to a hidden escape ship, leaving Clio in the hands of the Union. With everything she knows threading away into the stars, Stacia sets her heart on a single mission: She will find and rescue Clio, even with the whole galaxy on her trail"--Publisher's description.